2017
DOI: 10.1039/c6ra26542a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of human hair fiber-impregnated chitosan beads functionalized with citric acid for the adsorption of lysozyme

Abstract: Herein, a novel CA-CS/HHF composite was firstly constructed by impregnating human hair fiber into a CS matrix and then functionalized with citric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The characteristic absorption bands of APP at 3400-3000, 1430, 1242, 1072, 1016, and 877 cm −1 are ascribed to -NH 4 + , -NH 4 + , P=O, PO (symmetric stretching), PO 2 , and POP/PO (asymmetric stretching), respectively [12]. The characteristic absorption bands observed at 3500-3300, 1620, 1430, 1378, 1160, 1079, and 1032 cm −1 for CS are ascribed to -OH and -NH 2 , C=O, O-H, (CN, amide), (CO, bridge oxygen), (COC component), and (COC component), respectively [13][14][15]. The FTIR spectrum of APP-CS showed no apparent differences as compared with that of APP.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic absorption bands of APP at 3400-3000, 1430, 1242, 1072, 1016, and 877 cm −1 are ascribed to -NH 4 + , -NH 4 + , P=O, PO (symmetric stretching), PO 2 , and POP/PO (asymmetric stretching), respectively [12]. The characteristic absorption bands observed at 3500-3300, 1620, 1430, 1378, 1160, 1079, and 1032 cm −1 for CS are ascribed to -OH and -NH 2 , C=O, O-H, (CN, amide), (CO, bridge oxygen), (COC component), and (COC component), respectively [13][14][15]. The FTIR spectrum of APP-CS showed no apparent differences as compared with that of APP.…”
Section: Resultsmentioning
confidence: 99%
“…The MB adsorption isotherm was examined using Langmuir, Freundlich, and Dubinin–Radushkevich equilibrium isotherm models, using the following expressions, respectively (Equations 7–9; Tran et al, 2017; Xu et al, 2017): qnormale=qnormalmCnormaleKnormalL1+CnormaleKnormalL qnormale=KnormalFCnormale1nnormalF qnormale=qDReKDRε2 where q m (mg g −1 ) is the maximum adsorption capacity, K L (L mg −1 ) is the Langmuir equilibrium constant (Das & Pal, 2016). R L , the separation factor constant, was calculated according to Equation (10) and listed in Table 3 in the range of (0 < R L <1), suggest that the adsorption of CAR‐DTAB and CAR‐KCl on MB is appropriate (Doshi et al, 2018; Hai et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The MB adsorption isotherm was examined using Langmuir, Freundlich, and Dubinin-Radushkevich equilibrium isotherm models, using the following expressions, respectively (Equations 7-9; Tran et al, 2017;Xu et al, 2017):…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…For instance, Chen and co-workers developed the drug-loaded CA-modified CS hydrogels with application in wound dressing [16]. Xu's study reported the synthesis of CS beads functionalized with CA soaked with human hair fiber with high lysozyme adsorption capacity [17]. In another study, Rajan formu-lated cisplatin-loaded CS-based nanocomposites crosslinked with poly-oxalates and CA as potential carriers for controlled and targeted anticancer therapy [18].…”
Section: Introductionmentioning
confidence: 99%